2019
DOI: 10.3846/jbem.2019.8250
|View full text |Cite
|
Sign up to set email alerts
|

Do the Fama and French Five-Factor Model Forecast Well Using Ann?

Abstract: Forecasting the stock returns in the emerging markets is challenging due to their peculiar characteristics. These markets exhibit linear as well as nonlinear features and Conventional forecasting methods partially succeed in dealing with the nonlinear nature of stock returns. Contrarily, Artificial Neural Networks (ANN) is a flexible machine learning tool which caters both the linear and nonlinear markets. This paper investigates the forecasting ability of ANN by using Fama and French five-factor model. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The choice of the method was based on the advantages it confers compared to other procedures. Thus, it was observed that NNs contribute to an increase in the predictability of stock prices compared to conventional methods (Sahiner et al, 2021), capture information in a more comprehensive manner (Chang et al, 2022), have a high error tolerance (Mijwel, 2018), accurately process sets of homogeneous data (Castello & Resta, 2022;Tripathi et al, 2022), demonstrate a better long-term predictive power compared to statistical methods (Jan & Ayub, 2019), and are superior to regression models or those based on the approach technique (Ozdemir & Tokmakcioglu, 2022). Compared to linear models, NNs can provide solutions to complex relationships without being reprogrammed (Caliskan Cavdar & Aydin, 2020;Talwar et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of the method was based on the advantages it confers compared to other procedures. Thus, it was observed that NNs contribute to an increase in the predictability of stock prices compared to conventional methods (Sahiner et al, 2021), capture information in a more comprehensive manner (Chang et al, 2022), have a high error tolerance (Mijwel, 2018), accurately process sets of homogeneous data (Castello & Resta, 2022;Tripathi et al, 2022), demonstrate a better long-term predictive power compared to statistical methods (Jan & Ayub, 2019), and are superior to regression models or those based on the approach technique (Ozdemir & Tokmakcioglu, 2022). Compared to linear models, NNs can provide solutions to complex relationships without being reprogrammed (Caliskan Cavdar & Aydin, 2020;Talwar et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The methods recently used in the study of the volatility of financial assets identified by the authors included logistic regression (Chang et al, 2022), stochastic dominance of the second order (Ozdemir & Tokmakcioglu, 2022), multivariate regression based on a deep neural network with backpropagation algorithm and Bayesian network (Naveed et al, 2023), traditional econometric models Neuro Fuzzy, ANFIS and CANFIS, EGARCH and VaR (Sahiner et al, 2021), Analytic Hierarchy Process (AHP) method, ANN based on FF5F model factors (Jan & Ayub, 2019), and ANN based on the multilayer perceptron model as a machine learning algorithm (Khansari et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant examples of this are the works by Trafalis and Ince (2000), or Wei-Yang, Ya-Han, and Chih-Fong (2012), or Wong, Fortino, and Abbott (2020), where models based on this technology are presented, providing a framework compatible with the prediction of the Great Depression of 2008 (Yu et al, 2014), and a useful tool for the prediction of crisis situations in financial institutions. Financial activity has been one of the most relevant fields of application of this new AI (Jan & Ayub, 2019;Weng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%